RESPONSE OF JOJOBA (SIMMONDSIA CHINENSIS, LINK) PLANTS TO COMPOST AND SOME STIMULATING SUBSTANCES TREATMENTS - M.A.H. Abdou; M. Aly; R. Taha; F. Badran; M. Ahmed (Scientific Journal of Flowers and Ornamental Plants, 2022)
This work was done during the two experimental seasons of 2020 and 2021 at the farm of Faculty of Agriculture, Minia University, Egypt to study the reaction of jojoba (Simmondsia chinensis, Link) plants to compost (0.0, 500, 1000 and 1500 g/container) and some stimulating substances (control, vitamin E at 100 ppm, active yeast at 10 g/l and garlic extract at 10%) treatments. Data revealed that increasing the level of compost led to a significantly increased in plant height, main stem thickness, number of branches/plant and aerial parts and root weights (fresh or dry) compared with control. While sprayed plants with all stimulating substances significantly enhanced all previous characters compared with the control. It can be concluded that the high level of compost (1500 g/container) plus yeast at 10 g/l or garlic extract at 10% led to the greatest growth parameters of jojoba plant